(untitled) (Palestine Issues on Indonesian Society, 2024)
This paper explores the role of social media in shaping Indonesian public discourse on Palestine, particularly through the engagement of youth and activists. The study investigates how social media platforms, such as Twitter, Instagram, and TikTok, have become critical tools for advocacy, mobilization, and the dissemination of information about the Palestinian cause. By examining the use of hashtags like #FreePalestine and #SaveAlAqsa, the paper highlights how digital activism in Indonesia has played a significant role in building solidarity with Palestine, especially among younger generations. The research also analyzes the ways in which Indonesian activists utilize these platforms to counter mainstream media narratives, promote awareness of the Palestinian struggle, and call for action on social and political issues related to Palestine. Furthermore, the paper addresses the challenges of misinformation and online censorship in the digital activism space, shedding light on the intersection of social media, politics, and youth engagement in Indonesia.